2015
DOI: 10.1093/ndt/gfv308
|View full text |Cite
|
Sign up to set email alerts
|

Early renal graft function deterioration in recipients with preformed anti-MICA antibodies: partial contribution of complement-dependent cytotoxicity

Abstract: Preformed anti-MICA antibodies may occasionally be cytotoxic by fixing and activating complement. This way they might contribute to worse early kidney graft function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Similarly, Zhang et al [ 20 ] in their study discussed that the antibodies against MICA were positive in 15 out of the 52 patients (28.9%). A retrospective study involving 727 renal allograft recipients published by Sánchez-Zapardiel et al [ 21 ] revealed a 7.15% prevalence of anti-MICA antibodies in patients waiting for a renal transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Zhang et al [ 20 ] in their study discussed that the antibodies against MICA were positive in 15 out of the 52 patients (28.9%). A retrospective study involving 727 renal allograft recipients published by Sánchez-Zapardiel et al [ 21 ] revealed a 7.15% prevalence of anti-MICA antibodies in patients waiting for a renal transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the serial quantification and monitoring of MICA MFI levels could alter the clinical management of allograft rejection and need to be assessed in large randomized, prospective trials. Sánchez-Zapardiel et al [ 21 ] reported that preformed anti-MICA antibodies significantly increased the risk for allograft rejection particularly early after transplantation and that this effect was independent of the presence of anti-HLA antibodies. However, no significant difference was noticed in allograft survival and rejection rates at 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphic MICA molecules are constitutively expressed on vascular endothelial cells, and previous experiments revealed that increased MICA expression levels were associated with hypoxic stress conditions accompanying transplantation [ 8 ]. Although the adverse effects of anti-AT1Rs or anti-MICA on allograft outcomes have been demonstrated in several studies [ 9 10 11 12 13 14 ], the clinical significance of pre-transplant non-HLA antibodies remains controversial, and studies on the association between non-HLA antibodies and histological outcomes are limited.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MICA antibodies were reported to cause cell death through complement-dependent cytotoxicity [ 29 ]. A very recent research showed that 23% of anti-MICA-positive sera from pretransplant patients could fix C1q and further confirmed that the deleterious effect of MICA antibodies relied on fixation and activation of the complement cascade [ 30 ]. All these data indicate an indispensable role of complement system in the pathogenesis of MICA antibodies.…”
Section: Endothelial Cells As Targets In Antibody-mediated Rejectimentioning
confidence: 98%